CULTURE CHANGE: CASE OF THE USE OF TRADITIONAL INSTRUMENTS REPLACED WITH MODERN INSTRUMENTS IN KERONCONG MUSIC - Dani Nur Saputra (Universitas Negeri Medan, 2020)
As the development of science, technology, and external culture, individuals and groups face the challenges and major influences that enable changes in one's values, attitudes, and thinking patterns. Keroncong music is one type of music that is a result of the culture of society, especially the Javanese community. In technological developments, the existence of traditional music has been replaced by modern music. The method used in this study is a qualitative research method with a descriptive analytical approach. Technique of data analysis performed using reduction of the data, the presentation of the data, and verification. the results show that cultural change in case of instrument musical change in Keroncong music effected by lack of relationship with other societies, developed education system, attitude of valuing the work of others and strong desire to advance, open system society (open stratification), vested interest, existence of reclusive attitude and prejudice against new (foreign), barriers which are ideologically, custom or habit that has rooted, value that life This is in fact.